Management of Unsatisfactory Postoperative Double Eyelid With Intralesional Corticosteroid Injection - Zhang, Siyi; Zhou, Yixiong; Yu, Fei; Yan, Dan; Yan, Yan; Zhou, Meng; Fu, Yao; Lu, Yang (Frontiers in Medicine, 2021)
Purpose: The present study was designed to observe the curative effect of early intralesional corticosteroid injection to treat unsatisfactory double eyelid. Methods: This retrospective, observational study included 30 female patients (age 22–35 years) receiving intralesional corticosteroid injection after complaining about the unsatisfactory double eyelid post-transcutaneous upper eyelid blepharoplasty. The postoperative double eyelid anomalies included multiple folds, sunken eyelids, and severe postoperative eyelid edema. The evaluation of the clinical effect was based on the bilateral symmetry of the eyelid, the placement of the lid fold, the radian of the double eyelid, and the extent of the swelling and depression. Results: Multiple folds were observed in 11 (36.67%) patients, sunken eyelids in 9 (30.00%) patients, and severe postoperative eyelid edema in 10 (33.33%) patients. Among them, 17 (56.67%) patients received one intralesional injection and experienced significant improvement in the eyelid, while 8 (26.67%) accepted another injection at 1 month after the first injection and achieved marked improvement. The remaining 5 (16.67%) patients were dissatisfied with the results and might need further repair surgery: 2 patients had multiple folds, 2 showed postoperative edema, and 1 presented sunken eyelids. None of the patients reported any adverse reactions. Conclusion: Intralesional corticosteroid injection for the correction of the postoperative unsatisfactory double eyelid is safe and convenient, and provides a novel method for early intervention.